Self-motivated visual scanning predicts flexible navigation in a virtual environment - Ploran, Elisabeth J.; Bevitt, Jacob; Oshiro, Jaris; Parasuraman, Raja; Thompson, James C. (Frontiers in Human Neuroscience, 2014)
The ability to navigate flexibly (e.g., reorienting oneself based on distal landmarks to reach a learned target from a new position) may rely on visual scanning during both initial experiences with the environment and subsequent test trials. Reliance on visual scanning during navigation harkens back to the concept of vicarious trial and error, a description of the side-to-side head movements made by rats as they explore previously traversed sections of a maze in an attempt to find a reward. In the current study, we examined if visual scanning predicted the extent to which participants would navigate to a learned location in a virtual environment defined by its position relative to distal landmarks. Our results demonstrated a significant positive relationship between the amount of visual scanning and participant accuracy in identifying the trained target location from a new starting position as long as the landmarks within the environment remain consistent with the period of original learning. Our findings indicate that active visual scanning of the environment is a deliberative attentional strategy that supports the formation of spatial representations for flexible navigation.